Jane Austen Speaks Norwegian The Challenges of Literary Translation - Nedregotten Sørbø, Marie (Costerus New Series, 2018)
Can Jane Austen only be fully understood in English? In Jane Austen Speaks Norwegian, Sørbø compares novels and their translations, while also discussing the strategies chosen by translators of literature. Readership: Students and researchers of English literature and translation, Jane Austen societies, and women's studies and reception studies groups.